2017
DOI: 10.1155/2017/2148139
|View full text |Cite
|
Sign up to set email alerts
|

The Better You Feel the Better You Learn: Do Warm Colours and Rounded Shapes Enhance Learning Outcome in Multimedia Learning?

Abstract: The aim of the present study was to examine whether fostering positive activating affect during multimedia learning enhances learning outcome. University students were randomly assigned to either a multimedia learning environment designed to induce positive activating affect through the use of "warm" colours and rounded shapes ( = 61) or an affectively neutral environment that used achromatic colours and sharp edges ( = 50). Participants learned about the topic of functional neuroanatomy for 20 minutes and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 71 publications
(113 reference statements)
0
19
0
Order By: Relevance
“…Research has also confirmed the role of color in emotional design. To illustrate, Münchow et al (2017) applied warm color designs to learning material on neuroanatomical topics and indicated that, compared with gray-scaled designs, warm color designs improved comprehension and transfer performance of learners. Plass et al (2019) further verified that warm colors in teaching games were related to the positive emotions of participants.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has also confirmed the role of color in emotional design. To illustrate, Münchow et al (2017) applied warm color designs to learning material on neuroanatomical topics and indicated that, compared with gray-scaled designs, warm color designs improved comprehension and transfer performance of learners. Plass et al (2019) further verified that warm colors in teaching games were related to the positive emotions of participants.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…However, recent research regarding the emotional and cognitive effects yielded mixed results. Some studies found the positive emotional design on visual elements could not only induce positive emotions but also facilitate cognitive outcomes including cognitive load and learning performance (Um et al, 2012;Mayer and Estrella, 2014;Plass et al, 2014Gong et al, 2017a;Münchow et al, 2017;Brom et al, 2018;Schneider et al, 2018;Uzun and Yıldırım, 2018). For example, Plass et al (2014) designed learning materials with warm color and baby-like shape design and found it could induce learners' positive emotions, decrease perceived difficulty and promote learning performance.…”
Section: Emotional Design Through Visual Designmentioning
confidence: 99%
“…They found similar results (e.g., reduced perceived task difficulty, increased learning), but unlike Um et al(2012)'s study, Plass et al (2014) found emotional design made no difference to knowledge transfer. The positive effect of emotional design on people's learning and intrinsic motivation were replicated to some extent in other studies (e.g., Münchow et al, 2017;Schneider et al, 2016). However, multiple studies failed to elicit a positive affect with emotional design (e.g., Mayer & Estrella, 2014;Münchow et al, 2017).…”
Section: Affective Theory Of Multimedia Learning and Emotional Designmentioning
confidence: 61%